Exosome-transmitted miR-3124-5p promotes cholangiocarcinoma development via targeting GDF11 - Gao, Huijie; He, Zhaobin; Gao, Chao; Liu, Naiqing; Zhang, Zhaoyang; Niu, Weibo; Niu, Jun; Peng, Cheng (Frontiers in Oncology, 2022)
Objective: Cholangiocarcinoma (CHOL) is a deadly cancer worldwide with limited available therapies. This study aimed to investigate key exosomal miRNAs and their functions in CHOL development. Methods: Serum exosomes were isolated from patients with CHOL and healthy controls, followed by miRNA sequencing for identifying differentially expressed miRNAs (DEMs) and their functions. Then, the expression of key DEMs was experimental validated in exosomes from clinical CHOL patients and CHOL cells. The effects of overexpression of key DEMs on CHOL cell migration and proliferation were investigated. A key exosomal DEM miR-3124-5p was identified. The effects of overexpression or knockdown of exosomal miR-3124-5p on the proliferation, migration, and angiogenesis of human umbilical vein endothelial cells (HUVECs) were investigated. Moreover, the function of exosomal miR-3124-5p on tumor growth in vivo was explored. Results: A total of 632 exosomal DEMs were identified between CHOL and control samples. Target genes of DEMs were significantly enriched in pathways, such as p53 signaling pathway. miR-3124-5p was up-regulated in serum exosomes from CHOL patients and exosomes from CHOL cells, and overexpression of miR-3124-5p promoted RBE cell migration and viability. Moreover, overexpression of exosomal miR-3124-5p promoted the proliferation, migration, and angiogenesis of HUVECs, while knockdown of miR-3124-5p had opposite effect. miR-3124-5p could target growth differentiation factor 11 (GDF11) and downregulate GDF11 expression. Furthermore, exosomal miR-3124-5p promoted tumor growth in vivo. Conclusions: Our findings revealed that exosome-encapsulated miR-3124-5p promoted the malignant progression of CHOL by targeting GDF11. Exosomal miR-3124-5p and GDF11 could be promising biomarkers or therapeutic targets for CHOL.